Cytokine concentration in aqueous humor of eyes with diabetic macular edema - Jonas, Jost B.; Neumaier, Michael; Findeisen, Peter (Retina, 2012)
Purpose: To measure cytokine concentrations in aqueous humor of eyes with diffuse diabetic macular edema. Methods: The interventional clinical comparative study included a study group of 23 patients with diffuse diabetic macular edema and a control group of 22 patients undergoing cataract surgery. Cytokine concentrations were measured in aqueous humor samples using a Luminex xMAP suspension array technology. Results: In the study group as compared with the control group, significantly higher concentrations were measured for epidermal growth factor (P < 0.001), human growth factor (P < 0.001), intercellular adhesion molecule-1 (ICAM-1; P < 0.001), interleukin (IL)-1a2 (P = 0.04), IL-6 (P = 0.001), IL-8 (P < 0.001), interferon gamma-induced protein (P = 0.004), monocyte chemoattractant protein-1 (P < 0.001), monokine induced by interferon gamma (P < 0.001), matrix metalloproteinase 1 (P = 0.02), matrix metalloproteinase 9 (P < 0.001), plasminogen activator inhibitor 1 (P < 0.001), placenta growth factor (P < 0.001), tissue growth factor beta (P = 0.003), vascular cell adhesion molecule (P < 0.001), and vascular endothelial growth factor (P < 0.001). Retinal macula thickness was significantly associated with the concentrations of the epidermal growth factor (P = 0.005; ρ = 0.45), ICAM-1 (P < 0.001; ρ = 0.65), IL-3 (P = 0.002; ρ = 0.48), IL-6 (P = 0.003; ρ = 0.47), IL-8 (P < 0.001; ρ = 0.71), monocyte chemoattractant protein-1 (P = 0.001; ρ = 0.53), monokine induced by interferon gamma (P < 0.001; ρ = 0.57), matrix metalloproteinase 9 (P < 0.001; ρ = 0.61), tissue growth factor beta (P = 0.01; ρ = 0.42), placenta growth factor (P = 0.004; ρ = 0.46), vascular cell adhesion molecule (P = 0.006; ρ = 0.44), and vascular endothelial growth factor (P = 0.01; ρ = 0.42). In multivariate analysis, macular thickness remained to be significantly associated with the concentration of ICAM-1 (P = 0.03; r = 0.30). Vascular endothelial growth factor concentrations were correlated with concentration of placenta growth factor (P < 0.001; ρ = 0.78), plasminogen activator inhibitor 1 (P = 0.001; ρ = 0.54), ICAM-1 (P < 0.001; ρ = 0.47), monokine induced by interferon gamma (P = 0.004; ρ = 0.44), monocyte chemoattractant protein-1 (P = 0.003; ρ = 0.43), vascular cell adhesion molecule (P = 0.01; ρ = 0.38), IL-6 (P = 0.02; ρ = 0.35), IL-8 (P = 0.02; ρ = 0.37), epidermal growth factor (P = 0.01; ρ = 0.39), and macrophage migration inhibitory factor (P = 0.01; ρ = 0.37). Conclusion: Numerous cytokines are associated with the presence and the amount of diabetic macular edema. Among these cytokines, ICAM-1 was the most significantly associated with the disease parameters.